KAJIAN TERHADAP PEMILIHAN MEDIA DAN PENGIMPLEMENTASIANYA BAGI PESERTA DIDIK JENJANG SEKOLAH DASAR - Ryan Apriansyah; Yunisa Azahra; Futri Nur Insani; Usep Setiawan (LPPM STKIP PGRI Sidoarjo, 2023)
The development of the modern era and today's technology certainly influences all aspects and various fields, especially in the field of education. Of course, many of us feel the developments in the field of education as well as in the learning process. One of them is learning media. Through this article, we try to study and examine learning media whose content is about the study of how to choose and how to implement this learning media for students at the elementary school (SD) level. With learning media, it will certainly make students more enthusiastic and motivated when in the learning process and with the use of learning media, competencies and learning objectives will be more easily achieved. And for students at the elementary school level (SD) they really need media aids/intermediaries because according to Piaget's learning theory, at this stage the child is only able to group the shape of an object but has not yet reached the stage of solving an abstract problem. Indicators of the success of learning media can be seen when students are able to answer questions posed by educators both orally and in written tests.